Online learning environment to enhance HOTS in mathematics using Polya's problem solving model - Mustapha, S. (2019)
Low Higher Order Thinking Skills (HOTS) among students is a persistent and pervasive challenge in modern classroom. The problem remains for years despite the intensive manoeuvres to solve it. Yet, the need to enhance HOTS is imperative in ensuring quality education. The purpose of this research is to enhance HOTS among students in Mathematics using an online learning environment. The online learning environment was developed based on Polya's problem solving model. However, the system is not discussed in this paper. There are three research objectives which are to investigate the current HOTS achievement among students, to study the effect of the developed online learning environment in nurturing HOTS among samples and finally to study how learning process taken place to achieve HOTS among sample while engaging the system. This research implemented experimental research design with a set of pre and posttest and the developed online learning environment as intervention. A total of 76 samples were sampled for the preliminary study and another 32 samples for the four weeks treatment using cluster random sampling technique. Samples are from three schools from a district in Malaysia. Finding shows that the current HOTS achievement among students are still low at mean = 32.05, σ = 15.87. During the intervention, samples show improvement in their HOTS from mean = 39.52, σ = 11.65 in the pretest to higher level in the posttest at mean = 77.84, σ = 12.84. The Paired-Samples T Test conducted to identify the differences between the pre and posttest shows a statistically significant difference at t (31) = -11.58, p < 0.05. Indicating that an online learning environment using Polya's problem solving for four weeks enhance HOTS among samples. The process of how samples achieve HOTS is also reported. This research shows the importance of integrating technology and inquiry in modern classroom to increase students' thinking skill ability. Finding suggests that HOTS can be nurtured via technology enhanced learning environment.